2008
DOI: 10.1177/0950017008096740
|View full text |Cite
|
Sign up to set email alerts
|

Have stethoscope, will travel: contingent employment among physician health care providers in the United States

Abstract: A B S T R AC TThe goal of this study was to describe locum tenens physicians in the context of contingent, nonstandard employment in the US. The target population for this study was 1662 physicians who accepted at least one locum tenens assignment. Response rate for the 50-item questionnaire was 47 percent. One third of respondents considered a locum tenens practice pattern permanent. Female physicians were younger and disproportionately represented in primary care specialism; 64 percent used locum income as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…The phenomenon of contingent and nonstandard employment in the hospital context is relatively new but can be observed in several countries, e.g. the US and the UK (Alonzo & Simon, 2008;De Ruyter, Kirkpatrick, Hoque, Lonsdale, & Malan, 2008;Houseman, Kalleberg , & Erickcek, 2003;Kirkpatrick & Hoque, 2006;Simon & Alonzo, 2004). Houseman et al (2003) analyzed agency work of nurses and showed that, in contrast to hospitals, agencies were able to recruit nurses and other hospital professionals by paying them more than hospitals did.…”
Section: Physicians' Employment In German Hospitalsmentioning
confidence: 99%
“…The phenomenon of contingent and nonstandard employment in the hospital context is relatively new but can be observed in several countries, e.g. the US and the UK (Alonzo & Simon, 2008;De Ruyter, Kirkpatrick, Hoque, Lonsdale, & Malan, 2008;Houseman, Kalleberg , & Erickcek, 2003;Kirkpatrick & Hoque, 2006;Simon & Alonzo, 2004). Houseman et al (2003) analyzed agency work of nurses and showed that, in contrast to hospitals, agencies were able to recruit nurses and other hospital professionals by paying them more than hospitals did.…”
Section: Physicians' Employment In German Hospitalsmentioning
confidence: 99%
“…Other research in health care shows that implementation of functional flexibility could result in significant stress, intensification of work, and learning new skills (Desombre et al, 2006). Further research in health care shows that temporary staff physicians appreciate their work situation (Alonzo and Simon, 2008).…”
Section: The Flexible Organization and Learningmentioning
confidence: 99%
“…A number of high‐skill occupations are subject to contingent status, including business consultants (Donnelly, ), travelling physicians (Alonzo and Simon, ), itinerant IT experts (Barley and Kunda, ) and a variety of portfolio workers ( e.g. freelance writers) (Mallon and Duberley, ; Clinton et al ., ; Redpath et al ., ).…”
Section: Cckwsmentioning
confidence: 99%
“…What results from the intersection of these two continuums are four types of contingent knowledge workers. Dimensions of work can vary within professions as much as between them, but as shown in Figure , the industry research lab, travelling physician and business consultant represent three types of knowledge workers studied in HRM (Alonzo and Simon, ; Donnelly, ; Fiore, ). The upper left‐hand quadrant is what this article refers to as the fourth type of knowledge workers – the collaborative contingent knowledge workers (CCKWs) , a new type of knowledge professional whose work takes place in the contingent and collaborative intersection.…”
Section: Cckwsmentioning
confidence: 99%